Scalable single-step synthesis of lignin-based liquid polyols with ethylene carbonate for polyurethane foams. (June 2022) - Duval, A.; Vidal, D.; Sarbu, A.; René, W.; Avérous, L.
Abstract: A new method for the synthesis of lignin-based liquid polyols was developed. Organosolv lignin was reacted with ethylene carbonate in polyethylene glycol as solvent, leading to a full conversion of the phenolic OH into primary aliphatic OH groups. These aromatic polyols are obtained in a single step, without any purification. Upon modification of the polyethylene glycol molar mass, a wide range of hydroxyl values ( I OH ) can be covered. The polyols with up to 30%wt lignin have a viscosity suitable for the direct elaboration of polyurethane (PUR) foams. The method presents significant advantages over oxypropylation, the most common method for producing lignin-based polyols since it is performed at ambient pressure, without any toxic chemicals, does not require purification or post treatment, and allows to produce polyols with tunable properties. Four different aromatic polyols were then synthesized to produce rigid PUR foams, with substitution of up to 100% of a standard polyether polyol. The developed polyols showed very high reactivity, allowing to reduce the catalyst content in the PUR formulation by 75%. Rigid PUR foams prepared with 25% substitution of the standard polyol showed properties in the range of commercial PUR foams, with more than 90% closed cells and thermal conductivity of about 25 mW m −1 /K, perfectly adequate for thermal insulation applications. Highlights: New, green, and safe synthetic strategy to obtain active lignin-based polyols. Strong advantages compared to the conventional oxypropylation synthesis. Simplified production of polyols covering a larger IOH range with low viscosity. Synthesis performed at low temperature and atmospheric pressure. The synthesis does not require any specific equipment.